Pleuropulmonary Blastoma (PPB) in an infant: Is the timing of an elective resection of neonatal lung lesions challenged? - Robert Simon; Elizabeth McIntyre; Paras Khandhar; Jacqueline Macknis; Anne C. Fischer (Elsevier, 2014)
Congenital Pulmonary Airway Malformations (CPAMs) are abnormalities of lung parenchyma that are often diagnosed upon prenatal imaging as opposed to postnatal symptoms. With a clinical presentation identical to CPAMs, Pleuropulmonary Blastoma (PPB) is a rare pulmonary neoplasm of highly malignant potential. We present a rare case of a female infant with a vague medical history of respiratory distress syndrome (RDS) at birth, presenting with a tension pneumothorax at three months of age, thought initially to be secondary to CPAM, but found to be PPB upon surgical resection and histological analysis. PPB is a rare pulmonary neoplasm of childhood that originates from the primitive interstitium of the lung, resulting in lesions that can be highly malignant. It is classified as type I (cystic), type II (cystic/solid) or type III (solid), with a progression of disease and worsening prognosis from type I to type III. Due to the cystic nature of CPAM and PPB it is difficult to differentiate on imaging alone; diagnosis must be made based on histological analysis. The highly malignant nature and potential for morbidity and mortality of PPB should make clinicians consider early resection of cystic lung lesions preferentially on an elective basis.